Criminology in the Arab World: misconceptions, Nuances and Future Prospects - Ouassini, Nabil (The British journal of criminology, 2020)
In the protests that occurred throughout the Arab world, the criminal justice system has been the focal contention between citizens and the state. However, the notoriety of Arab regimes has compelled academics to devote their endeavours to political/religious violence, economic development/stagnation and the durability of undemocratic systems that has inhibited the production of criminological scholarship. The study of criminology in the Arab world is critical and necessitates special attention. The following article propounds the establishment of an Arab criminology sub-field that highlights strategies in research in the region, evaluates the current approaches, addresses the challenges and examines its implications on southern, international and comparative criminology.